Acoustic voice assessment in Parkinson's disease patients submitted to posteroventral pallidotomy Parametros acústicos da voz em pacientes com doença de Parkinson submetidos a palidotomia posteroventral - Lucia Figueiredo Mourão; Patrícia Maria de Carvalho Aguiar; Fernando Antônio Patriani Ferraz; Mara Suzana Behlau; Henrique Ballalai Ferraz (Arquivos de Neuro-Psiquiatria)
Long-term complications in levodopa treated Parkinson's disease (PD) patients caused a resurgence of interest in pallidotomy as an option of treatment. However, postoperative complications such as speech disorders can occur. PURPOSE: The aim of this study is to evaluate the acoustic voice in PD patients, before and after posteroventral pallidotomy. METHOD: Twelve patients with PD were submitted to neurological and voice assessments during the off and on phases, in the pre-operative, 1st and 3rd post-operative months. The patients were evaluated with the UPDRS and the vocal acoustic parameters - f0, NHR, jitter, PPQ, Shimmer, APQ (using the software MultiSpeech - Kay Elemetrics - 3700). RESULTS: The off phase UPDRS scores revealed a tendency to improvement at the 1st month and the off phase worsened. The shimmer and APQ improved. CONCLUSION: This study shows that pallidotomy has little improvement on functional use of communication of PD patients. O uso prolongado da levodopa na doença de Parkinson (DP) pode ocasionar alterações em seu rendimento e possibilitou o interesse no ressurgimento da palidotomia. Contudo, complicações pós-operatórias podem ocorrer. OBJETIVO: O presente estudo tem por objetivo avaliar alguns parâmetros acústicos da voz de pacientes com DP pré e pós a realização da palidotomia posteroventral METODO: foram avaliados 12 pacientes com PD submetidos a avaliação neurológica e da voz durante as fases off e on do uso da levodopa, nos momentos pré-operatório, no primeiro e no terceiro mês pós-operatório. Os pacientes foram avaliados com base na escala UPDRS - item motor - e por meio dos parâmetros acústicos da voz - f0, NHR, jitter, PPQ, Shimmer, APQ (usando o software MDVP - Kay Elemetrics - 3700). RESULTADOS: Na fase off o escore UPDRS revelou tendência de melhora no 1º pós-operatório e na fase on piora. Os parâmetros acústicos shimmer e APQ apresentaram melhora. CONCLUSÃO: Este estudo mostrou que a palidotomia resulta em discreta melhora no uso funcional da comunicação dos pacientes com DP.